Cleantech Industry Survey 2023: Financing, regulatory, innovation and human capital issues - Andrea Odille Bosio; Annalisa Croce; Laura Toschi; Elisa Ughetto (European Investment Fund (EIF), 2024)
This paper highlights the main challenges faced by the Cleantech sector. Key barriers include limited access to external finance, with many respondents expecting to raise significant funds in the next five years. Additionally, stringent and uncertain standards and regulations create operational challenges. Expanding our understanding of the Cleantech sector can enhance targeted support schemes to accelerate clean technology adoption, reduce greenhouse gas emissions, and improve environmental sustainability. This is the latest paper resulting from a project on "The cleantech industry in the European Green Deal: policy challenges and the finance landscape for SMEs" (CLEU), initiated by EIF's Market Assessment and Research Division. Funded by the EIB Institute's University Research Sponsorship (EIBURS) programme, the project aims to enhance our understanding of the Cleantech sector and improve the design of support schemes to accelerate the green transition in the EU. The EIF Working Papers are designed to make available to a wider readership selected topics and studies in relation to EIF's business. The Working Papers are edited by the EIF and are typically authored or co-authored by EIF staff or are written in cooperation with EIF.
Keywords: 330